Development of STEM-Based E-Learning on Renewable Energy Topic to Improve the Students Creative Thinking Skills - Nauratun Nazhifah; Ketang Wiyono; Ismet Ismet (Postgraduate, University of Mataram, 2023)
Education has a major role in facing the challenges of the 21st-century through Education for Sustainable Development (ESD). The Merdeka Curriculum came as an idea to change the quality of education in Indonesia. However, the availability of learning resources is still very low, not yet phenomenon-based, multidisciplinary, and not oriented toward improving 21st-century skills. This has an impact on the low creative thinking skills of students. These skills are a necessity and can only be produced through phenomenon-based learning, studied in multidisciplinary ways, such as STEM learning. It is necessary to develop learning resources such as STEM-based e-learning. This study aims to develop STEM-based learning that is feasible and acceptable using the Alessi and Trolip development model. The research subjects were students of class X of SMAN 2 Palembang. The results showed that the alpha test of the product was suitable for use with an acceptable percentage of 100%. The beta test results of the product can be accepted by 100% of students. This study concludes that STEM-based renewable energy e-learning to improve the creative thinking skills of high school students has been feasible and acceptable to students. Furthermore, it can be used for the effectiveness test stage.